Sumber dan Penyelesaian Konflik dalam Penanganan Kebijakan Konflik di Sekolah - Agripina Candraningtyas; Muslimatul Afiyah; Mirza Gunawan Wibisono; Novi Nur Amalia; Mualimin Mualimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Conflicts occur in the school environment not only cause obstacles, but also provide solutions in the implementation of school policies. This article discusses the sources and resolution of conflict in the implementation of conflict management policies in schools. This research aims to identify the sources of obstacles in implementing conflict management policies in schools and provide solutions in the form of policy-based solutions that can be implemented effectively. This research is a qualitative approach, descriptive research, and literature study data collection method. Previous research that discussed the same issue showed a lack of training for educators and limited resources. The findings show that: First, the conflict management policy implemented in schools is done by identifying the sources of conflict. Second, conflict resolution in schools can be done by avoidance, accommodation, confrontational approach, compromise, and collaborative problem solving